Pengaturan Penyitaan Aset Kripto sebagai Hasil Tindak Pidana Pencucian Uang di Indonesia - Halim Hermanto; Lolita Fitriyana (CV Rewang Rencang, 2025)
This study examines the legal vacuum surrounding the confiscation of crypto assets derived from money laundering within Indonesia’s legal system. Although crypto assets are recognized as investment commodities, Indonesia lacks specific procedures that address their digital nature, resulting in technical obstacles and legal uncertainty. A comparative analysis with Australia and the United States shows that both jurisdictions have established comprehensive regulatory frameworks integrating AML/KYC obligations and digital asset confiscation procedures. This study highlights the need for Indonesia to reform its regulations to ensure legal certainty and adapt to the evolving crypto-asset landscape.